2021
DOI: 10.2147/idr.s288869
|View full text |Cite
|
Sign up to set email alerts
|

Renal Involvement in COVID-19: A Review of the Literature

Abstract: Kidney injury may be a severe complication of acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and contributes to worsen the prognosis. Various pathophysiological mechanisms can contribute to organ damage and impair renal function, proving the complexity of the virus activity and the resulting immunity response. We summarized the evidence of the literature on the prevalence of kidney involvement, on the pathogenic pathways and on its management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 61 publications
(71 reference statements)
0
38
0
1
Order By: Relevance
“…It is more frequent in critically ill patients. Different mechanisms have been described: Direct effect of the virus and secondary mechanisms linked to the hemodynamic (hypo-perfusion), thrombotic micro-angiopathy, humoral response to the virus, and activation of the complement system [41]. Histologically, nonspecific acute or subacute tubular necrosis was observed in five of our patients and none of them had lymphocyte infiltration.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…It is more frequent in critically ill patients. Different mechanisms have been described: Direct effect of the virus and secondary mechanisms linked to the hemodynamic (hypo-perfusion), thrombotic micro-angiopathy, humoral response to the virus, and activation of the complement system [41]. Histologically, nonspecific acute or subacute tubular necrosis was observed in five of our patients and none of them had lymphocyte infiltration.…”
Section: Discussionmentioning
confidence: 65%
“…Acute renal failure was also common and related to decompensated chronic vascular and diabetic nephropathies. The incidence of acute kidney injury (AKI) during SARS-CoV-2 infection varies from 0.5% to 80.3% [41]. It is more frequent in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Rhabdomyolysis is commonly observed in COVID-19. It can lead to high levels of serum phosphokinase creatinine (more than five times the upper bound of ordinary) and could be another critical factor in ARI development [65].…”
Section: Renal Involvementmentioning
confidence: 99%
“…Another study from France reported 47% patients with confirmed COVID-19 had anosmia 11 . The pathophysiological mechanism underlying the occurrence of anosmia is still not wellunderstood, but two explanations have been proposed 12 .…”
Section: Table-v Distribution Of Factors Associated With In Hospital Outcome Of Study Population (N=769)mentioning
confidence: 99%
“…However, most affected individuals are healthy asymptomatic carriers or have minor symptoms 3 . SARS-CoV-2 not only involves lung, but may also affect the cardiovascular system [4][5][6] , gastrointestinal system 7,8 , central nervous system [9][10][11] , renal system 12 and skin 13 . The SARS-CoV-2 protein characteristic spike binds to its cellular receptor, the angiotensin-converting enzyme 2 (ACE2), which is widely expressed in many cell types and organs like lung alveolar cells, nasal epithelium, cerebral cortex, digestive tract, kidney, gallbladder, testis, and adrenal gland 11 .…”
Section: Introductionmentioning
confidence: 99%